Procedure and protocols for optical imaging of cerebral blood flow and hemodynamics in awake mice - Li, Yuandong (Biomed Opt Express, 2020)
We describe a method and procedure that allows for the optical coherence tomography angiography (OCTA) and intrinsic optical signal imaging (IOSI) of cerebral blood flow and hemodynamics in fully awake mice. We detail the procedure of chronic cranial window preparation, the use of an air-lift mobile homecage to achieve stable optical recording in the head-restrained awake mouse, and the imaging methods to achieve multiparametric hemodynamic measurements. The results show that by using a collection of OCTA algorithms, the high-resolution cerebral vasculature can be reliably mapped at a fully awake state, including flow velocity measurements in penetrating arterioles and capillary bed. Lastly, we demonstrate how the awake imaging paradigm is used to study cortical hemodynamics in the mouse barrel cortex during whisker stimulation. The method presented here will facilitate optical recording in the awake, active mice and open the door to many projects that can bridge the hemodynamics in neurovascular units to naturalistic behavior.